Correction: Band gap and photo charge carrier tailoring in zirconium doped carbon nitride using ZrCl4DMFmelamine for photocatalytic degradation of rhodamine B - Chinathun Pinming; Qingshan Yang; Navaphun Kayunkid; Visittapong Yordsri; Ki Kang Kim; Winadda Wongwiriyapan; Young Jae Song (My University, 2025)
Correction for ‘Band gap and photo charge carrier tailoring in zirconium doped carbon nitride using ZrCl 4 –DMF–melamine for photocatalytic degradation of rhodamine B’ by Chinathun Pinming et al. , J. Mater. Chem. A , 2025, https://doi.org/10.1039/D4TA09247C.
Keywords: Rhodamine B; Degradation; Carbon nitride; Graphitic carbon nitride; Advanced Nanomaterials in Catalysis